Quick practice basic accounting / Marshita Hashim ... [et al.] - Hashim, Marshita; Mahmud, Radziah; Abdul Manan, Nor Suhailati; Md Nor, Nor Hayati; Azizan, Siti Sakinah (UiTM Press, 2019)
The aim of this book is to allow students to understand basic accounting concepts and practise through practical exercises. After many years of teaching several accounting courses to various undergraduates accounting and non-accounting students, we believed that there was a need for a book that can provide various exercises for non-accounting students to better understand this course and able to pass their accounting paper's examination with flying colours. Many textbooks provide detailed description of accounting treatments and practices, however, this book is written mainly to provide students with many different types of questions in order to help them prepare themselves for the examination. The topical questions are arranged in a manner that can help the students to understand better the basic accounting topics.